instrumen asesmen untuk mengukur keterampilan sains siswa MI pada topik energi terbarukan:kajian literatur - Shilfany Putri; Sukiman; Sintha Sih Dewanti (Jurnal Penelitian Pendidikan IPA, 2025)
The assessment of science skills in science education at the Madrasah Ibtidaiyah (MI) level is very crucial. Through this assessment, teachers can assess the extent to which students are able to apply science process skills related to renewable energy. Science process skills are fundamental competencies that must be improved from the basic education stage, because they play a role in improving critical thinking skills, problem solving, and a deep understanding of science. However, the assessment of science process skills in MI still faces many obstacles, such as a lack of valid and trusted measuring instruments, and a lack of linkages to contextual issues such as renewable energy. Renewable energy is an important international issue in addressing the energy crisis and climate change, so its understanding must be taught from the beginning. This study aims to evaluate various existing assessment instruments to measure the science process skills of MI students when discussing renewable energy topics, using a literature review. The results of the study showed that the most widely applied assessment instruments included performance tests, assessment rubrics, observation sheets, portfolios, and project-based evaluations. The instrument not only focuses on the cognitive aspect, but also covers the psychomotor and affective dimensions of students, also showing that there are still shortcomings in the assessment instruments that specifically measure the science skills of MI students regarding the theme of renewable energy. Therefore, it is necessary to develop a more comprehensive, inquiry-based, and appropriate assessment tool in accordance with the characteristics of MI students. This research emphasizes the importance of creating contextual, authentic, and skill-oriented assessment instruments for science process skills to improve the quality of science learning in MI.